Strengthening Traditional Technical Knowledge : The Sugar Cane Wine Example - Luzietoso, Nguala; Bom Khonde, Paul Charles; Bazabana, Jean Jacques Magloire (World Bank, Washington, DC, 2012)
In the context of globalization, local African products already in high demand, could be successfully marketed nationally, and internationally. This holds true for the traditional sugar cane wine making in parts of West Africa, namely, Angola, Congo, and the Democratic Republic of Congo. The note expands on the local knowledge process, used in making this wine: an ancestral practice, transmitted from to generation to generation, which contributes to job creation, and is a source of income for small processing enterprises. The growing demand for sugar cane wine has a stimulus effect on its production, and is increasing the need for equipment, and packaging. Sugar cane technology, and knowledge transmission is emerging, particularly within producer groups, and associations. Two methods of apprenticeship are identified: from elder to younger generations, and, knowledge sharing. The prospects regarding this indigenous technical knowledge are vast regarding African economic development, but constraints, such as low productivity, storage problems, and lack of bottling techniques, prevent the full marketing process to attain commercial benefits. Researchers, nongovernmental organizations, and entrepreneurs should strengthen this indigenous knowledge, by combining same with transfer mechanisms from science and technology, research and development institutes, and back to the local communities. This approach could trigger a new dynamism of economic activity.